Diastolic filling pattern and left ventricular diameter predict response and prognosis after cardiac resynchronisation therapy. Issue 8 (5th November 2007) - Gradaus, R; Stuckenborg, V; Löher, A; Köbe, J; Reinke, F; Gunia, S; Vahlhaus, C; Breithardt, G; Bruch, C
Abstract : Objective: To investigate predisposing factors for cardiac resynchronisation therapy (CRT) response. Design: Single-centre study. Setting: University hospital in Germany. Patients: 122 consecutive patients with heart failure (mean (SD) age 65 (11) years; ischaemic/non-ischaemic 41%/55%; New York Heart Association (NYHA) class 3.1 (0.3); left ventricular ejection fraction 24.4 (8.1)%; QRS width 170 (32) ms, quality of life (QoL) 43.5 (19.2)) with an indication for CRT and demonstrated left ventricular dyssynchrony by echocardiography including tissue Doppler imaging. Interventions: Besides laboratory testing of clinical variables, results of ECG, echocardiography including tissue Doppler imaging, invasive haemodynamics, measures of QoL and of exercise capacity were obtained before CRT implantation and during follow-up. Main outcome measure: Responders were predefined as patients with improvement by one or more NYHA functional class or reduction of left ventricular end-systolic volume by 10% or more during follow-up. Mean (SD) follow-up was 418 (350) days. Results: Overall, 70.5% of patients responded to CRT. Responders had a significantly improved survival compared with non-responders (96.2% vs 45.5%, log-rank p<0.001). On univariate analysis, left ventricular end-diastolic diameter, left ventricular end-systolic diameter (LVESD), E/A ratio, a restrictive filling pattern, mean pulmonary artery pressure, pulmonary capillary pressure, N-terminal pro-brain natriuretic peptide and Vo 2 max were significant predictors of outcome. On multivariate analyses, LVESD (p = 0.009; F = 7.83), pulmonary capillary pressure (p = 0.015, F = 6.61) and a restrictive filling pattern (p = 0.026, F = 5.707) remained significant predictors of response. Conclusions: Despite treatment according to present guidelines nearly 30% of patients had no benefit from CRT treatment in a clinical setting. On multivariate analyses, patients with an increased left ventricular end-systolic diameter and concomitant diastolic dysfunction had a significantly worse outcome.